A graphene-based sensor for real time monitoring of sun exposure. (November 2018) - Khiabani, Parisa S.; Kashi, Mehran B.; Zhang, Xiao; Pardehkhorram, Raheleh; Markhali, Bijan P.; Soeriyadi, Alexander H.; Micolich, Adam P.; Gooding, J. Justin
Abstract: The photoreduction of graphene oxide (GO) with titanium dioxide (TiO2 ) was exploited to fabricate a UV sensor for real time monitoring of sun exposure. The sensor was fabricated by simultaneous deposition of GO sheets and TiO2 nanoparticles onto interdigitated electrodes using an AC electrophoresis deposition method. Changes in the resistance of the GO sheets decorated with TiO2 nanoparticles during repeated cycles of exposure to UV were measured to understand the sensitivity of this sensor to UV radiation. Current-time traces revealed that the fabricated UV sensor retains a memory of each cycle of UV exposure; regardless of whether the sensor is exposed to UV for one long cycle or several short cycles. This memory of the extent of UV exposure is a biomimetic approach, analogous to the response of the skin to sun, and means the sensor requires no power except when the data is read from the sensor. Graphical abstract: Image 1